Pengolahan Citra dengan Metode Ekstraks Deteksi Mata Manusia Berbasis I Fitur - Setiawan Syah Zebua (Bulletin of Computer Science Research, 2020)
The eye functions to see and interpret the shapes, colors, and dimensions of objects in the world by processing the light reflected by objects that give off light. Visual disturbances or eye diseases often occur in people so that they interfere with their daily activities. Moving or staying still can provide information about the human condition. From the information obtained from eye detection, it can be concluded that an eye movement. Measuring eye movement is psychophysical work and to obtain information about a person's level of unconscious behavior, strategies to process eye movement information require fixation and knowledge of the direction of the gaze. Feature extraction is a feature / feature retrieval from a form where the value obtained will be analyzed for further processing. Feature extraction is done by counting the number of dots or pixels found in each check. The features obtained from an image are the distinguishing characteristics of other images.